Possible Implication of Fcγ Receptor-Mediated Trogocytosis in Susceptibility to Systemic Autoimmune Disease - Sakiko Masuda; Sari Iwasaki; Utano Tomaru; Tomohisa Baba; Kazuaki Katsumata; Akihiro Ishizu (Clinical and Developmental Immunology)
Leukocytes can “gnaw away” the plasma membrane of other cells. This phenomenon, called trogocytosis, occurs subsequent to cell-to-cell adhesion. Currently, two mechanisms of trogocytosis, adhesion molecule-mediated trogocytosis and Fcγ receptor-(FcγR-) mediated trogocytosis, have been identified. In our earlier study, we established an in vitro model of FcγR-mediated trogocytosis, namely, CD8 translocation model from T cells to neutrophils. By using this model, we demonstrated that the molecules transferred to neutrophils via FcγR-mediated trogocytosis were taken into the cytoplasm immediately. This result suggests that the chance of molecules transferred via FcγR-mediated trogocytosis to play a role on the cell surface could be time-limited. Thus, we consider the physiological role of FcγR-mediated trogocytosis as a means to remove antibodies (Abs) that bind with self-molecules rather than to extract molecules from other cells. This concept means that FcγR-mediated trogocytosis can be a defense mechanism to Ab-mediated autoimmune response. Moreover, the activity of FcγR-mediated trogocytosis was revealed to be parallel to the endocytotic activity of neutrophils, which was critically related to the susceptibility to systemic autoimmune diseases. The collective findings suggest that FcγR-mediated trogocytosis could physiologically play a role in removal of Abs bound to self-antigens and prevent autoimmune diseases.